The role of adaptive leadership in achieving sustainable performance: A study of the opinions of a sample of employees in a number of private banks in Duhok Governorate - Wessi, Dr. Omar Hussein Wessi (Sulaimani Journal for Humanities, 2026)
The current research aims to shed light on sustainable performance, which represents one of the most prominent contemporary issues challenging business organizations globally. Therefore, this research sought to identify the role of adaptive leadership in achieving sustainable performance in private banks in Duhok Governorate. Accordingly, we proceeded to measure adaptive leadership as an independent variable and then examine the level of sustainable performance as a dependent variable, in order to bridge the knowledge gap between these two variables. To achieve this, a hypothetical framework was constructed to illustrate the relationship between the research variables, focusing on the correlation between adaptive leadership and its impact on sustainable performance. The research adopted a descriptive analytical approach, and a questionnaire was used to collect primary data. A sample of employees from private banks in Duhok Governorate was selected, and 44 valid questionnaires were obtained for analysis. Frequencies, percentages, arithmetic means, and standard deviations were used to describe and analyze the study variables. The correlation coefficient was used to determine the relationship between the two variables, and the regression coefficient was used to determine the impact of the independent variable on the dependent variable. The data was analyzed using SPSS v. 27. After analyzing the data, the current study reached several conclusions, including the importance of adaptive leadership and sustainable performance in private banks in Duhok Governorate. There is a strong and positive correlation between adaptive leadership and sustainable performance, and adaptive leadership significantly impacts the sustainable performance of private banks in Duhok Governorate. Accordingly, the study suggested that the leaders of the surveyed banks should possess qualities that enable them to take appropriate action at the right moment and motivate employees to pay attention to environmental, economic, and social issues.
Keywords: Adaptive Leadership; Sustainable Performance; Private Banks in Duhok